Wh-Movement, Islands, and Resumption in L1 and L2 Spanish: Is (Un)Grammaticality the Relevant Property? - Perpiñán, Sílvia (Frontiers in Psychology, 2020)
This study reflects on the meaning of the results of an online grammaticality judgment task that tested island configurations (with gaps and resumptive pronouns) in L1 and L2 speakers of Spanish. Results indicated that resumptive pronouns do not rescue extractions from islands, as usually assumed in grammatical theory, and propose that islands are essentially an interpretative or processing matter, and not a grammatical one, as in Kluender (1998). This study further challenges the L2 studies that proposed that L2 learners are fundamentally different to native speakers because they usually fail to reject island configurations, and shows that, L2 learners are sensitive to the same processing and interpretative mechanisms that native speakers employ to parse island configurations. Generally speaking, this study proposes that apparent purely syntactic restrictions such as extractions from islands might not depend on their grammatical formation, but on other relevant factors such as plausibility, embedding, and processability, which together with well-formedness should configure a more holistic notion of linguistic grammaticality.